Curricular Policies for a cultural and linguistic formation: evidences of a political option for a unilateral and neocolonial international socioeconomic development - Rocha, Sandro Silva; Monte Mor, Walkyria (The ESPecialist, 2024)
This article presents a summary of two studies made by Leffa (1999) and Rodrigues (2016) on the laws modifying the Brazilian national curricular policies on foreign language teaching and learning. Comparatively, it aims to research the laws practiced in São Paulo and other countries, constituted by a linguistic and cultural diversity, inherent or as a consequence of intense migratory flows. To analyze the results of this research, some theoretical tools proposed by Hall (1997), Castro-Gómez (2007), Monte Mor (2013), and Spolsky (2016) are used. The results show that the Brazilian policies for foreign language teaching, despite having already valued plurilingualism at some points, in other, especially the current one, have submitted its students to a monolingualist and monoculturalist point of view, resulting from the globalizing process of Americanization of the world. The results have also demonstrated the necessity of the existence of investments and tools to demand a closer fiscalization on the implementation of such laws.